Frequency of Nephrotic Syndrome in children - Said, Haya; Ali, Liaqat; Talaat, Azmat (Journal of Postgraduate Medical Institute, 2011)
To findout the frequency of childhood nephrotic syndrome and its rleation to different solar months. This study was conducted in paediatrics departmetn of LRH, Peshawar first August 1995 to 31st July 1996. All children with proteinuria and oedema were studied. All children were thoroughly examined and investigated. nephrotic syndrome in fairly common in children with male preponderance. Most admission due to nephrotic syndrome were in the month of january.